1986
DOI: 10.1007/bf02230422
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 monitoring in human CSF after subarachnoid hemorrhage: the possible role of prostaglandin D2 in the genesis of cerebral vasospasm

Abstract: Experimental and clinical studies indicate that cerebral vasospasm following subarachnoid hemorrhage (SAH) may be caused by changed biochemical properties of the endothelium and vascular smooth muscle cell exposed to vasoactive substances synthetized by cerebral arteries and released in clotted blood. Many compounds have been identified in CSF from SAH patients: Thromboxanes A2 and B2, Prostaglandins F2 alpha, E2 and D2 are the major prostanoids incriminated in the causation of cerebral arterial spasm. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Both Toda [32] and Lang and Maron [33] suggested that a variety of cyclooxygenase inhibitors could interfere with the effects of oxyhemoglobin or whole blood, al though these agents are ineffective in clinical vasospasm in man. Cerebrospinal fluid from patients with cerebro vascular spasm apparently contains elevated levels of prostaglandins, particularly prostaglandin D2 [17] and prostaglandin F 2a [ 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Toda [32] and Lang and Maron [33] suggested that a variety of cyclooxygenase inhibitors could interfere with the effects of oxyhemoglobin or whole blood, al though these agents are ineffective in clinical vasospasm in man. Cerebrospinal fluid from patients with cerebro vascular spasm apparently contains elevated levels of prostaglandins, particularly prostaglandin D2 [17] and prostaglandin F 2a [ 15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that since eicosanoids may be formed in cerebral vessels as well as brain parenchyma [ 13] and can also be released from platelets and by stimulation of the brain cortex [14], these substances should be considered as factors involved in the regulation of cerebral blood flow and in the patho genesis of vasospasm. Eicosanoids, such as prostaglandin F 2a [15], prostaglandin E2 [16], prostaglandin D2 [17] and thromboxane A2 [18], were increased and prostaglandin I2 [19] was decreased during the development of vaso spasm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, at such concentrations PGD 2 concentrations the natural response of T lymphocytes via the DP1 receptor is to inhibit interferon gamma (IFN-y) production; IFN-y possesses anti-tumor properties (Sandig et al, 2007;Schroder et al, 2004). Considering that human cerebral spinal fluid (CSF) contains between 0.4nM to 5.3nM PGD 2 and PGD 2 has a strong affinity for DP2, an argument could be made that PGD 2 's endogenous presence in the CSF could support GBM survival (Gaetani et al, 1986). Even though our results showed that micromolar PGD 2 had no effect on cell viability, there was a very significant increase in cell count.…”
Section: The Impact Of Pgd 2 On Cellular Activitymentioning
confidence: 99%